2018
DOI: 10.12659/msmbr.910660
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship Between Markers of Oxidative Stress, Inflammation and Hematological Parameters Among Preeclamptic Nigerian Women

Abstract: BackgroundPreeclampsia is a multifaceted pregnancy-related disorder affecting women and fetuses. A link between preeclampsia, oxidative stress, and inflammation has been suggested. This study evaluated the interrelationship between biomarkers of oxidative stress, inflammation, and hematological parameters among preeclamptic Nigerian women.Material/MethodsA cross-sectional study was conducted among 49 preeclamptic and 50 normotensive healthy pregnant women. Blood samples were obtained after 20-week gestation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
2
10
0
1
Order By: Relevance
“…Left ventricular involvement in preeclampsia is thought to cause cardiac ischemia, which can result in changes in several biomarkers of heart function. 16 This study is consistent with the study of Morton et al which measured hscTnI levels in 40 asymptomatic preeclamptic women results showed that hscTnI levels increased by 25% of the sample. Echocardiographic studies that were also carried out showed the presence of diastolic dysfunction in about 20% of women with preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…Left ventricular involvement in preeclampsia is thought to cause cardiac ischemia, which can result in changes in several biomarkers of heart function. 16 This study is consistent with the study of Morton et al which measured hscTnI levels in 40 asymptomatic preeclamptic women results showed that hscTnI levels increased by 25% of the sample. Echocardiographic studies that were also carried out showed the presence of diastolic dysfunction in about 20% of women with preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…In the pathogenesis of PE, the balance between oxidants and antioxidants is broken, being one of the key features of PE (Haram, Mortensen, Myking, Magann, & Morrison, ). Ekun et al indicated lower SOD and higher MDA levels in PE women's blood samples, suggesting the association of PE with oxidative stress (Ekun et al, ). It is illustrated that flavonoids, including VI derivatives, can protect against oxidative stress‐damaged liver in mice (Lorizola et al, ), indicating the antioxidant property of VI.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in GDM (13). It is caused by an imbalance between the oxidant and the antioxidant (14). Oxidative stress is considered to be a causative factor in human pregnancy-related diseases, such as fetal death, pre-eclampsia, and intrauterine growth restriction (15).…”
Section: Introductionmentioning
confidence: 99%